The effect of human capital on survival of SMEs in food processing under economic crisis in Central Java, Indonesia - Agussalim M; Palmarudi Mappigau (Proceedings of AICS - Social Sciences, 2013)
The objective of this study is to analyze  the effect  of human capital on  survival of SMEs in  food processing in Central Java Indonesia during the economic crisis. As much as 102 small firms with traditional beef processing and preservation which produce Jerked beef and Beef Floss were choosen as samples. Primary and secondary data have been collected in 2009 when the global economic crissis hitand analyzed using path analysis. This study concluded that; (a) human capital such as motivation and industrial experience in the same field have positive effect on entreprepreneur’s competencies, adaptation strategy and survival of the firms. However, effect from the motivation tend to be larger than industrial experience; (b) Entrepreneur’s competencies have positive effect on the adaptation strategy and survivalof the firms. However, the contribution effect of the entrepreneurial competency tend to be larger than the managerial competency; (c) adaptation strategy has positive effect on the survival of the firms; and (d) human capital have effect on the survival of the firms through entreprenerur’s competencies (entreprepreneurial and managerial competencies) and adaptation strategy.A better understanding of this finding will benefit the implication ofthe future research about the survival of small food processing firms under economic resession aspects. Also it will help policymaker in supporting improved competitiveness of the small food processing firms and improving human capital for SMEs entrepreneurs in Indonesian.Keyword: Human capital, entreprenerur’s competency, adaptation strategy, firm survival, SME in  food processing